2018
DOI: 10.1088/1361-6560/aae24c
|View full text |Cite
|
Sign up to set email alerts
|

A multi-criteria optimization approach for HDR prostate brachytherapy: I. Pareto surface approximation

Abstract: High dose rate (HDR) brachytherapy planning usually involves an iterative process of refining planning objectives until a clinically acceptable plan is produced. The purpose of this two-part study is to improve current planning practice by designing a novel inverse planning algorithm based on multi-criteria optimization (MCO). In the first part, complete Pareto surfaces were approximated and studied for prostate cases. A Pareto surface approximation algorithm was implemented within the framework of Inverse Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…In contrast to a more recently introduced multicriteria optimization approach that requires pretrained regression models to guide the optimization toward clinically acceptable plans, our bi‐objective evolutionary optimization approach requires no prior training, because it directly calculates all relevant DV indices throughout optimization. As our bi‐objective evolutionary optimization approach requires between 30 and 300 seconds, we have shown that it is indeed possible to approximate a surface of trade‐off plans within a clinically acceptable time frame.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to a more recently introduced multicriteria optimization approach that requires pretrained regression models to guide the optimization toward clinically acceptable plans, our bi‐objective evolutionary optimization approach requires no prior training, because it directly calculates all relevant DV indices throughout optimization. As our bi‐objective evolutionary optimization approach requires between 30 and 300 seconds, we have shown that it is indeed possible to approximate a surface of trade‐off plans within a clinically acceptable time frame.…”
Section: Discussionmentioning
confidence: 99%
“…2.1.1 Patient selection An anonymous dataset that contains 562 prostate cancer patients who received an HDR brachytherapy treatment as a boost to EBRT from April 2011 to July 2016 at our institution was studied. This dataset incorporates the cases studied in prior works (Edimo et al 2019, Cui et al 2018a, Cui et al 2018b. Among the dataset, 100 random cases (validation set) were used to determine the number of Pareto optimal plans with the gMCO algorithm, and 462 random cases (test set) were used in the performance evaluation of the gMCO generated plans.…”
Section: Methodsmentioning
confidence: 99%
“…where N O is the number of organs, N pnt,j is the number of dose calculation points in the j th organ. w j is a hidden weight applied to the objectives (surface and volume) of the j th organ to introduce trade-off in the solution space around the population-based starting point as in (Cui et al 2018a, Cui et al 2018b. The hidden weights are always non negative and their sum is one (because of the weighted sum method).…”
Section: Quadratic Objective Function Formulationmentioning
confidence: 99%
See 2 more Smart Citations